The Palestinian-Israeli Ceasefire Proposal: Van Dijk’s Critical Discourse Analysis of Al-Arabiya’s Reporting - Salma, Hilda Ma’iisya; Chotimah, Dien Nur (Journal of Language and Literature Studies, 2025)
The ceasefire proposal between Israel and Palestine shocked the world’s residents because of the pros and cons of several related parties. Israel and Hamas as the target parties showed different responses to the proposal agreement presented by President Biden in his speech. So, this research is certainly considered interesting because it concerns the most important world phenomenon that has succeeded in shaking the global community. This research uses a qualitative method that aims to describe and analyze the discourse on this ceasefire proposal with the reactions of certain parties as stated in the Al-Arabiya news text based on Teun van Dijk’s critical discourse analysis through the text dimension. The results showed the following data findings: 1) macrostructure (theme); 2) superstructure (scheme) includes summary (title and lead) and story (comment and situation); 3) microstructure four studies include semantic (background, detail, intent, presupposition, and nominalization), syntax (sentence form, coherence, and pronoun), stylistic (lexicon), and rhetoric (graphic, metaphor, and expression). The three structures have various elements with their characteristics to form the entire discourse content cohesively and relate to each other. Especially in the title and lead of the discourse, Al-Arabiya journalists have indirectly summarized the responses of those who accept or reject President Biden’s statement after understanding the news content.